An effective approach to routing problems - Stankovianska, Ida (Univerzita Pardubice, 2006)
The Clarke-Wright method is one of the commonly applied heuristic methods used for finding solutions of the vehicle routing problems. This paper describes differential modification of the original Clarke-Wright method.
Keywords: Optimalizace; směrování; dopravní procesy; heuristické metody; Algoritmy